Crack closure effect and crack growth behavior in GH2036 superalloy plates under combined high and low cycle fatigue. (February 2017) - Hu, Dianyin; Yang, Qian; Liu, Huawei; Mao, Jianxing; Meng, Fanchao; Wang, Yanfei; Ren, Mengxi; Wang, Rongqiao
Highlights: The crack closure is only present at low stress ratio for GH2036 superalloy. The large HCF amplitude and cycle ratio increase crack growth rate. Intergranular failure leads to an increased crack growth rate at a high cycle ratio. A new model is developed to describe crack growth behavior under CCF loading. Abstract: The present work aims to investigate the crack closure effect and crack growth behavior of GH2036 superalloy subjected to a combined high and low cycle fatigue (CCF) loading. GH2036 superalloy plates were tested under stress ratios of 0.1, 0.4, and 0.7 in order to examine the crack closure effect. Together with Digital Image Correlation measurement, it is found that crack closure is present at low stress ratio ( R < 0.7) and subsequently a crack closure model was developed. Moreover, experiments by varying high cycle fatigue (HCF) amplitude and cycle ratio were performed under CCF loading at 550 °C, showing increased crack growth rate under large HCF amplitude and cycle ratio while decreased crack growth rate under small HCF amplitude. Furthermore, a new CCF crack growth model incorporating the crack closure effect, time-independent crack increment, and transient vibrational analysis was proposed and validated by comparing with experimental results to be able to accurately predict fatigue crack growth life under different HCF amplitudes and cycle ratios. Finally, fractography analysis was also performed to discuss the mechanism underlying the crack growth behavior. Our study provides comprehensive and significant experimental and modeling insights into the crack growth behavior of superalloys under CCF loading.